UPLC/MSn analysis of Bougainvillea glabra leaves and investigation of antioxidant activities and enzyme inhibitory properties - Heba A. S. El-Nashar; Omayma A. Eldahshan; Mahmoud A. El Hassab; Gokhan Zengin; Esraa A. Elhawary (Scientific Reports)
Abstract Bougainvillea glabra is a well-known and well-documented ornamental plant belonging to family Nyctaginaceae, always planted for its beautifully colored flowers. The current study was performed for profiling the metabolites of B. glabra leaf extract. Further, the leaf extract was evaluated using the total phenolic and total flavonoid assays and profiling using UPLC/MSn for the leaf extract’s secondary metabolites. The leaf extract was also subjected to several antioxidant assays, viz. DPPH, ABTS, CUPRAC, FRAP, metal chelating, and phosphomolybdenum tests, as well as enzyme inhibition assays such as α-amylase, α-glucosidase, acetylcholinesterase (AChE), and butyrylcholinesterase (BChE). The results showed that the total phenolic and flavonoid contents were 27.68 mg GAE/g and 31.76 mg RE/g, respectively. Besides, twenty-one metabolites were tentatively identified and quantified, where flavonoids and phenolic acids constituted the most abundant classes of compounds. The molecular docking experimentss showed that the most abundant components, namely rhamnocitrin-O-rutinoside, sagerinic acid, tri-O-caffeoyl-shikimic acid, and chlorogenic acid, had the best scores when docked in the vicinity of the selected enzyme targets. The extract recorded a potentially powerful antioxidant activity, compared to the used standards, while it showed a good inhibitory effect against AChE (2.40 mg GALAE/g) and BChE (1.95 mg GALAE/g). The tyrosinase-inhibiting effect was 48.23 mg CAE/g. The amylase and glucosidase inhibitory effects were 0.30 mmol ACAE/g and 0.03 mmol ACAE/g, respectively. Thus, this study suggests that B. glabra may not only act as an ornamental plant, but also it may be a promising source for effective phytochemicals that act as antioxidants and enzyme inhibitors, which may play a role in reversing the aging process and age-related ailments like diabetes.